Analisis Perbandingan Metode Evaluasi Usability berbasis Pengguna pada Web-Based GIS (Studi Kasus: petabencana.id) - Andito Wahyudi; Fatwa Ramdani; Aditya Rachmadi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
This research is based on the development of usability in a web-based GIS. The purpose of this research is to compare the ability and depth of the user-based usability evaluation method in exploring problems in a web-based GIS. The data were collected from a group of respondents who were determined by the researcher using purposive sampling by evaluating the usability of each method. The methods included were usability testing (N = 5), user interviews (N = 10), and surveys (N = 20). A total of 61 usability problems were found using three methods. Usability testing found 28 problems (46%), interviews found 20 problems (32%), and the survey method found 13 problems (21%). Of the 28 problem categories according to the usability problem taxonomy (UPT), the usability testing method covers 21 categories (75%), while the interview method covers 17 categories (60%), and the survey method covers 13 categories (46%). The three methods complement each other because each method successfully covers a unique problem category. The combination of usability testing, interviews, and surveys can explore all problems and cover all problem categories in a web-based GIS.